Effect of molybdenum on microstructures in Zr-1.2Nb alloys after β-quenching and subsequently 873 K annealing. (15th August 2016) - Yang, H.L.; Kano, S.; Matsukawa, Y.; Li, Y.F.; Shen, J.J.; Li, F.; Zhao, Z.S.; Satoh, Y.; Abe, H.
Abstract: The effect of Mo addition on microstructures of β-quenched and subsequently annealed Zr-1.2Nb alloys is systematically investigated. Differential scanning calorimetry, electron backscatter diffraction, transmission electron microscopy, X-ray energy dispersive spectrometry techniques and microhardness tests are jointly utilized to characterize the microstructure and to evaluate the mechanical property. Martensitic microstructure, a mixture of lath martensites and lens martensites, is observed in the β-quenched specimens. Width of lath martensite reduces and fraction of lens martensite increases as the Mo content increases. This suggests that Mo addition retards slip deformation and enhances twinning deformation during the martensitic transformation, and that segregation of Mo atoms is also responsible for the lath width reduction. After annealing at 873 K, the martensitic structures are maintained, accompanying with the presence of numerous precipitates, which is attributed to the fact that the β-quenched microstructure is strain-relieved instead of being recrystallized. The distribution of the misorientation angle between the neighboring grains in both β-quenched and subsequently α-annealed specimens is predominantly around 60° regardless of the Mo content. Microhardness increases with increasing Mo content both in the β-quenched and the annealed specimens, and it drops greatly after annealing at a fixed composition. Graphical abstract: Highlights: The microstructural characterization on the β-quenched and the subsequently annealed Zr-Nb-Mo alloys were investigated. Lath martensites and lens martensites with internal twinning were coexisted after β-quenching. Doping of Mo reduced the width of lath martensite and increased the volume fraction of lens martensite. Microhardness increased with increasing Mo content in both cases, and it dropped after annealing at a fixed composition.